Analisis Kompetensi Guru dalam Pemanfaatan Inovasi dan Teknologi di SD YPPK St. Thomas Aquino Nohotif Kampung Urumb - Nurkholis Syukron; Mudatsir Mudatsir; Andri Irawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The relatively fierce competition of the modern era demands that every individual possess strong competitiveness in interpersonal interactions. Education serves to break the cycle of low-quality human resources through a range of programmes, thereby enhancing individual competitiveness. Teachers, as integral to academic activities, play a central role in driving the realisation of educational objectives. This study aims to determine how prepared teachers are to develop human resources within the educational environment and to identify efforts to enhance teachers’ competence in innovating and utilising technology. This study employs a qualitative approach using a descriptive method. The instruments used in this study are observation sheets, interview guidelines and questionnaires. The data analysis mechanism in this study involves data reduction, data presentation and drawing conclusions. This study was conducted at St. Thomas Aquino Nohotif Primary School, Urumb Village, Semangga District, Merauke Regency, South Papua Province. The sample was selected using purposive sampling. The research findings indicate that the majority of teachers are still unfamiliar with the use of information and communication technology tools in teaching and learning activities and have not yet fully mastered the management of administrative tasks or teaching materials, technology-based applications and innovations applied in learning—such as the use of artificial intelligence platforms, Kahoot, Google Meet and Google Classroom, Learning Houses, YouTube, WhatsApp, educational games and Canva—as well as strategic efforts to enhance teachers’ professional competence in the use of innovations and information and communication technology.